Creating healthy food environments in family childcare settings. (20th October 2021) - Kunkel, K; Schroeder, M; Jones, R; Anderson, D; Lien, K
Abstract: Background: Considering nearly two-thirds of preschool children in the United States are in some form of child care, child care settings are an opportunity to improve the food environments and reduce the risk of obesity in young children. University of Minnesota Extension developed a culinary nutrition education training for family child care providers. This is relevant for other countries whose child care system includes caring for children in home or center settings that prepare food for children. Objectives: Start Strong: Cooking, Feeding and More (SS), consists of four two-hour culinary nutrition education sessions for family providers. The overall goals of SS are to 1) increase providers' knowledge and skills to procure and prepare healthy foods for children and 2) increase providers' knowledge and understanding of Federal food assistance programs to share the information with food-insecure families. Each session includes a cooking skill, nutrition topic, and food assistance program. Results: Twelve rural participants who self-identified as female, non-Hispanic White participated in the SS sessions and completed pre, post, and three-month follow-up surveys, to assess the impact of the program on providers' knowledge, confidence, and practice. Based on the paired samples t-tests between pre-to-post and pre-to-follow-up surveys, there were statistically significant increases in providers' confidence in preparing whole grains, using beans and low-cost protein sources, and cooking techniques to reduce. The increase in confidence using cooking techniques to reduce salt was still statistically significant three months after the training. The providers' awareness of Federal food programs between pre-post increased and three months later increased. Conclusions: SS increased family child care providers' skills and confidence to prepare healthy foods for children in their care. This increases the likelihood children will make healthy choices now and in the future. Key messages: Start Strong is a culinary nutrition education training for family child care providers. Start Strong improves providers' knowledge and skills to prepare healthy foods for children in their care.